ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL ATAS PERSEDIAAN BARANG DAGANG PADA PT XYZ - Nadia Ayu Cahyaningsih, (2021)
This study is a qualitative research that aims to determine how the implementation of the internal control system for merchandise inventory according with the elements of the Committee of Sponsoring Organizations of Treadway Commission (COSO) and to find out whether PT XYZ has implemented an internal control system for merchandise inventory effectively. This study uses an interpretive paradigm and an ethnomethodology approach. Data collection techniques in this study are using interviews with key informants and supporting informants, and documentation. This study indicates that overall, PT XYZ has implemented an effective internal control system for merchandise inventory where the internal control procedures are following the elements of COSO control. However, there are still deficiencies, namely employees' inconsistency in implementing the company's Standard Operating Procedures (SOP), the risk of accidental elements such as human errors, weak authorization activities for transactions and activities, and inadequate SOP for selling merchandise.